Case reportLymphoepithelioma-like carcinoma of the skin in a Polish patient - Sobjanek, Michał; Dobosz, Magdalena; Pęksa, Rafał; Sokołowska-Wojdyło, Małgorzata; Kowalczyk, Anna; Michajłowski, Igor; Nowicki, Roman (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2015)
Lymphoepithelioma-like carcinoma of the skin (LELCS) is a very rare cutaneous neoplasm with limited metastatic potential. It presents distinctive histopathologic features similar to undifferentiated nasopharyngeal carcinoma and clinical similarities with other skin neoplasms. We present the first case of LELCS in Polish patients. A 72-year-old woman presented with a 12 months’ history of painless, solitary tumor on the nose. A wide local excision was performed. There was no evidence of local recurrence 24 months after surgical treatment.